Age‐dependent habitat relationships of a burned forest specialist emphasise the role of pyrodiversity in fire management. Issue 4 (21st January 2019) - Stillman, Andrew N.; Siegel, Rodney B.; Wilkerson, Robert L.; Johnson, Matthew; Tingley, Morgan W.
Abstract: Variation in fire characteristics, termed pyrodiversity, plays an important role in structuring post‐fire communities, but little is known about the importance of pyrodiversity for individual species. The availability of diverse post‐fire habitats may be key for fire‐associated species if they require different resources at different life‐history stages. We tested for age‐specific habitat relationships in the black‐backed woodpecker, a post‐fire specialist. We used radio‐telemetry to track fledgling and adult woodpeckers in burned forests and built resource selection functions to compare the effect of stand‐, tree‐ and snag‐level covariates between adults and fledglings. Fledgling black‐backed woodpeckers selected habitat with more live trees than adults and used more heterogeneous habitats burned at lower severity, illustrating strong age‐dependent effects on habitat selection. Within selected stands, fledglings were less likely to use snags and more likely to use live trees when compared to adults, but both age classes showed strong positive selection for larger‐diameter trees (live and dead). Over the 60 days after leaving their nests, fledglings showed an increasing propensity to use snags rather than live trees. Our results provide evidence that the predation–starvation hypothesis, which posits a trade‐off between foraging efficiency and the need to minimise predation risk, plays a role in structuring the age‐dependent habitat use of a burned forest specialist. Adult black‐backed woodpeckers selected resources associated with food availability, but these resources occurred in relatively open, exposed habitat. Fledglings selected habitat that provided increased cover, perhaps as a strategy to reduce predation risk. Synthesis and applications . Globally, fires are increasing in severity and extent, leading to increased focus on fire‐associated species that play keystone roles in facilitating biodiversity resilience. Our findings suggest that a diversity of patches burned at different severities may benefit post‐fire specialists like the black‐backed woodpecker at multiple life‐history stages. The increasing prevalence of large, homogeneously high‐severity 'megafires' may present an emerging threat even to post‐fire specialists, and we urge land managers to consider opportunities to promote pyrodiversity in the face of novel fire regimes. Abstract : Globally, fires are increasing in severity and extent, leading to increased focus on fire‐associated species that play keystone roles in facilitating biodiversity resilience. Our findings suggest that a diversity of patches burned at different severities may benefit post‐fire specialists like the black‐backed woodpecker at multiple life‐history stages. The increasing prevalence of large, homogeneously high‐severity 'megafires' may present an emerging threat even to post‐fire specialists, and we urge land managers to consider opportunities to promote pyrodiversity in the face of novel fire regimes.